Proteome changes in Arabidopsis thaliana roots upon exposure to Cd2+ - Roth, Udo (Journal of experimental botany, 2006)
Cadmium is a major environmental pollutant that enters human food via accumulation in crop plants. Responses of plants to cadmium exposure--which directly influence accumulation rates--are not well understood. In general, little is known about stress-elicited changes in plants at the proteome level. Alterations in the root proteome of hydroponically grown Arabidopsis thaliana plants treated with 10 microM Cd(2+) for 24 h are reported here. These conditions trigger the synthesis of phytochelatins (PCs), glutathione-derived metal-binding peptides, shown here as PC2 accumulation. Two-dimensional gel electrophoresis using different pH gradients in the first dimension detected on average approximately 1100 spots per gel type. Forty-one spots indicated significant changes in protein abundance upon Cd(2+) treatment. Seventeen proteins found in 25 spots were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Selected results were independently confirmed by western analysis and selective enrichment of a protein family (glutathione S-transferases) through affinity chromatography. Most of the identified proteins belong to four different classes: metabolic enzymes such as ATP sulphurylase, glycine hydroxymethyltransferase, and trehalose-6-phosphate phosphatase; glutathione S-transferases; latex allergen-like proteins; and unknown proteins. These results represent a basis for reverse genetics studies to better understand plant responses to toxic metal exposure and to the generation of internal sinks for reduced sulphur